Asset pricing on earnings announcement days - Chan, Kam Fong; Marsh, Terry (Journal of Financial Economics, 2022)
Market betas have a strong and positive relation with average stock returns on a handful of days every year. Such unique days, defined as leading earnings announcement days (LEADs), are times when an aggregate of influential S&P 500 firms disclose quarterly earnings news early in the earnings season. The positive return-to-beta relation holds for various test portfolios, individual stocks, and Treasuries; and is robust to different data frequencies and testing procedures. On days other than LEADs, the beta-return relation is flat. We conclude that waves of early earnings announcements by large firms clustered on LEADs significantly influence asset pricing.